2015
DOI: 10.1111/ffe.12330
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic fatigue performance of high temperature structural material Inconel 718 alloys at high temperature after UNSM treatment

Abstract: This study investigates the influence of ultrasonic nanocrystal surface modification (UNSM) technique on the mechanical characteristics and fatigue life of two types of annealed and aged Inconel 718 alloys. The mechanical properties of both UNSM‐treated alloys were compared with the untreated specimens. The fatigue life of the untreated and UNSM‐treated Inconel 718 alloy specimens was investigated by ultrasonic fatigue and rotary‐bending fatigue tests. Results revealed that the UNSM‐treated specimens exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Its mechanical and corrosion properties are maintained at temperatures as high as 700 • C, making the Inconel 718 alloy suitable for demanding working conditions [1,[4][5][6]. Among the high strength, fatigue, creep and wear resistance properties, Inconel 718 also has favorable weldability [7][8][9][10]. The outstanding mechanical and corrosion properties of Inconel 718 are attributed to its microstructure, which is mainly constituted of austenite, γ phase.…”
Section: Introductionmentioning
confidence: 99%
“…Its mechanical and corrosion properties are maintained at temperatures as high as 700 • C, making the Inconel 718 alloy suitable for demanding working conditions [1,[4][5][6]. Among the high strength, fatigue, creep and wear resistance properties, Inconel 718 also has favorable weldability [7][8][9][10]. The outstanding mechanical and corrosion properties of Inconel 718 are attributed to its microstructure, which is mainly constituted of austenite, γ phase.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies suggested that the fatigue strength of a material is proportional to its tensile strength and the fatigue crack that results in final failure usually initiates at the surface of the material [1][2][3]. In order to upgrade the fatigue strength of engineering materials/components, investigators have used surface strengthening techniques in the applications of aviation, automobile and high-speed railway [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It has similar microstructure and mechanical behaviour to those of Inconel 718. This kind of alloy has been widely utilized for fabricating modern aero‐engine components such as turbine discs, blades and cases for the reason that it has a good resistance to fatigue, oxidation and corrosion . There had been a few investigations on the small fatigue crack initiation and growth behaviour of Inconel 718 and nickel base superalloy GH4169.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of alloy has been widely utilized for fabricating modern aero-engine components such as turbine discs, blades and cases for the reason that it has a good resistance to fatigue, oxidation and corrosion. [10][11][12] There had been a few investigations on the small fatigue crack initiation and growth behaviour of Inconel 718 and nickel base superalloy GH4169. Goto et al 13 studied the fatigue damage of Inconel 718 at room temperature and 500°C.…”
Section: Introductionmentioning
confidence: 99%